Manifestation of universities “Third Mission” activities in universities’ ranking systems - Stonkienė, Marija; Matkevičienė, Renata (Information & Media, 2015)
In order to determine whether the universities’ ranking systems are treated in the context of implementation of universities’ third mission there was carried out scientific research, which has allowed to analyse the concept of the third mission of universities, to discuss the articulation of activities for implementation of the third mission of universities, to set indicators for analysis and evaluation of universities’ activities in the field. The analysis of the scientific researches has noted that the researchers of universities’ third mission are linked with the use of the knowledge generated by universities in academic, and as well in other contexts. In this way, the input of universities is presented based on the contribution of universities to meet the needs of society. It is noted that the third mission of universities first of all is associated with the “technology transfer”, and then manifestation of the third mission is related with “knowledge transfer”. Universities’ third mission analysis allowed identify two dimensions of the concept: entrepreneurship or based on economic input, and second is orientated toward meeting social needs. After studies of scientific investigations it was observed that the existing dimension of the universities third mission is determined both by the third mission of universities included in their activities, as well as the proposed system of indicators to evaluate universities’ third mission activities. After the analysis of methodologies for universities’ rankings, it was observed that in these ranking systems of universities third mission activities assessment is not provided as high-value. More attention is paid only for involvement of universities in technology transfer and innovation processes (such aspects of universities’ third mission as education and social inclusion (social engagement) activities are not evaluated). Observation results of most popular universities’ ranking methodologies show that activities carried out by universities in technology transfer and innovation processes are evaluated at different extent. Narrowest scope of those activities is indicated in the national rating systems methodologies, the most widely in U-Multirank universities’ rating methodology. Carried out study of selected universities ranking systems’ methodologies showed that in the rating methodology entrepreneurship / economic concept of the third mission of universities dimension can be seen as prevailing.